2017
DOI: 10.3390/ijms18020240
|View full text |Cite
|
Sign up to set email alerts
|

GGCX-Associated Phenotypes: An Overview in Search of Genotype-Phenotype Correlations

Abstract: Gamma-carboxylation, performed by gamma-glutamyl carboxylase (GGCX), is an enzymatic process essential for activating vitamin K-dependent proteins (VKDP) with important functions in various biological processes. Mutations in the encoding GGCX gene are associated with multiple phenotypes, amongst which vitamin K-dependent coagulation factor deficiency (VKCFD1) is best known. Other patients have skin, eye, heart or bone manifestations. As genotype–phenotype correlations were never described, literature was syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 66 publications
(98 reference statements)
1
55
0
Order By: Relevance
“…To extend our rat study on VKD proteins to human reproductive health, we identified a significant difference in the GGCX SNP mutation rs699664 in the asthenozoospermic samples compared with controls, but we found no differences in MGP. It is known that the GGCX rs699664 SNP mutation results in the amino acid change from 325Arg to Gln in GGCX (De Vilder et al., 2017) and is associated with bone density in elderly women (Kinoshita et al., 2007, Rieder et al., 2007). Asthenozoospermia is considered a common cause of male infertility characterized by a reduction in both sperm motility and normal sperm morphology (Sanchez-Alvarez et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To extend our rat study on VKD proteins to human reproductive health, we identified a significant difference in the GGCX SNP mutation rs699664 in the asthenozoospermic samples compared with controls, but we found no differences in MGP. It is known that the GGCX rs699664 SNP mutation results in the amino acid change from 325Arg to Gln in GGCX (De Vilder et al., 2017) and is associated with bone density in elderly women (Kinoshita et al., 2007, Rieder et al., 2007). Asthenozoospermia is considered a common cause of male infertility characterized by a reduction in both sperm motility and normal sperm morphology (Sanchez-Alvarez et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We next repeated the analysis using 812 IPAH cases only (all European) and observed significant associations for BMPR2 (p=1.0E-7, FDR=9.0E-04), KLK1 (p=1.0E-7, FDR=9.0E-04), GDF2 (p=3.0E-07, FDR=0.002) and GGCX (p=5.0E-07, FDR=0.002) ( Figure 4). GGCX encodes gamma-glutamyl carboxylase, implicated in coagulation factor deficiencies and ectopic mineralization of soft tissues 34 . These four genes were the only genes to reach genome-wide significance among IPAH cases.…”
Section: Identification Of Novel Pah Risk Genes: Klk1 and Ggcxmentioning
confidence: 99%
“…The vitamin K epoxide is recycled to reduced vitamin K by the vitamin K epoxide reductase (VKOR) enzyme complex [91,92]. GGCX is encoded by the gene located on chromosome 2 and VKORC1 is encoded by the gene present on chromosome 16 [93,94]. Mutations in these gene cause loss of GGCX or VKOR complex function and lead to vitamin K dependent coagulation factor deficiency [95].…”
Section: Vitamin K Dependent Coagulation Factors Deficiency (Vkcfd)mentioning
confidence: 99%